3/ 4x13/ 11x4 /13 13 /11
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a ) \(\dfrac{11.4-11}{13-2}=\dfrac{33}{11}=3\)
b ) \(\dfrac{25.13}{26.35}=\dfrac{325}{910}=\dfrac{5}{14}\)
= 4x4/3x7+ 4x4/7x11+ 4x4/11x15 = 4x(4/3x7 + 4/7x11+4/11x15) =4x(1/3-1/7+1/7-1/11+1/11-1/15) =4x(1/3-1/15)=4x4/15= 16/15.
= 4x4/3x7+ 4x4/7x11+ 4x4/11x15
= 4x(4/3x7 + 4/7x11+4/11x15)
=4x(1/3-1/7+1/7-1/11+1/11-1/15)
=4x(1/3-1/15)=4x4/15= 16/15.
\(\dfrac{-4}{3}-\dfrac{5}{7}+\dfrac{4}{3}=\left(\dfrac{4}{3}+\dfrac{-4}{3}\right)-\dfrac{5}{7}=0-\dfrac{5}{7}=-\dfrac{5}{7}\)
\(\dfrac{3}{13}\cdot\dfrac{6}{11}+\dfrac{3}{13}\cdot\dfrac{9}{11}-\dfrac{3}{13}\cdot\dfrac{4}{11}=\dfrac{3}{13}\cdot\left(\dfrac{6}{11}+\dfrac{9}{11}-\dfrac{4}{11}\right)=\dfrac{3}{13}\cdot1=\dfrac{3}{13}\)
Hình như đầu bài sai thì phải ạ!